Performance of Broiler Chickens Fed Diet Added with Buffaloes Rumen Fluid Enzymes from Slaughterhouses - Ucop Haroen; Agus Budiansyah; Noperdiman Noperdiman; Harnita Harnita; Jusalia Jusalia (Buletin Peternakan, 2019)
This study was conducted to evaluate the effect of addition of rumen fluid enzymes of buffaloes from slaughterhouse in diet on feed intake, slaughter weight, daily weight gain, feed conversion ratio, absolute carcass weight, relative carcass weight, and digestive organs of broiler. Materials used was two hundred unsexed 1 day old chicks of broilers. The study used a completely randomized design with five treatments and four replications consisted of 10 birds each replication. Treatment groups were as follows P0 = diet  without addition of rumen fluid enzymes (control); P1 = diet  with addition of rumen fluid enzymes of 0.75%; P2 = diet with addition of rumen fluid enzymes of 1.5%; P3= diet with addition of rumen fluid enzymes of 2.25%; P4=  diet with addition of rumen fluid enzymes of 3%. The variables observed were feed intake, slaughter weight, daily weight gain, feed conversion ratio, absolute carcass weight, relative carcass weight, and digestive organs. Results of the study showed that the treatments gave a non-significant different (P>0.05) on feed intake, slaughter weight, daily weight gain, feed conversion ratio, absolute carcass weight, relative carcass weight, and digestive organs of broiler chicken.  It could be concluded that the use of rumen fluid enzymes of buffaloes in the diets up to 3% level did not increase performance and digestive organs of broiler chicken.